Comunicare l'Università di Firenze Percorsi, sperimentazioni e prospettive - SORRENTINO, CARLO (Proceedings e report, 2014)
The volume presents the main results of the first two years of activity of the Laboratorio di comunicazione (Communication Laboratory) of the University of Florence, which brings together knowledge, skills and professionalisms operating within the Florentine University on the themes of institutional communication. Six contributions resulting from as many research paths, coordinated by Gaetano Aiello, Marco Biffi, Simone Guercini, Giuseppe Lotti, Saverio Mecca, Carlo Sorrentino and Luca Toschi, aimed at analysing the institutional identity of the University, its reputation in the various stakeholders, the paths of defining a clear coordinated image, the appropriateness of the language used.